Approaches to information-seeking behaviour in psychology: a comparison of early and contemporary studies - Thomas D. Wilson (Information Research: An International Electronic Journal)
Introduction.  The aim of this paper is to explore the investigation of information-seeking behaviour in the literature of psychology, with special reference to the period before 1981, when the term was introduced into information science, and compare the research of that period, with research reported in 2022-2023.